MITIGATION OF COVID-19 DISASTER IN SAWITSARI RESIDENCE ENVIRONMENT YOGYAKARTA - Napsiah Napsiah; Marfuah Sri Sanityastuti (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2021)
Abstract. The Covid-19 disaster mitigation is an action to break the chain of Covid-19 transmission. Mitigation can take the form of personal as well as collective actions. The purpose of this service is to demonstrate the efforts made by citizens collectively in cutting the transmission of Covid-19. By using the participant observation method because one of the community service teams is an administrator at the RW in Sawitsari Housing and the Focus Discussion Group (FGD) with the Rukun Warga (RW) and residents, this service activity results in the following programs: socialization social distinction through the installation of banners in residential areas and community meetings held before Yogyakarta was declared a Disaster Emergency Area. Lockdown or close the village to detect the mobility in and out of residents in the residential arena, and spraying disinfectants. These programs are the implementation of the Covid-19 health protocol program carried out by residents at the Rukun Warga (RW) level in a collective way.